Phytochemical screening and antibacterial activity testing of n-hexane extract from Barringtonia asiatica seeds - NURHAIDA, NURHAIDA; MURNIANA, MURNIANA; ATANTA, JAINURSUMARMI SAFRULLAH (Jurnal Natural, 2024)
Barringtonia asiatica, a marine plant belonging to the Lecythidaceae family, exhibits bioactivity in all parts of the plant. In the Simeulue region, the seeds of this plant are used for fish trapping. The polar extracts of B. asiatica seeds has shown antibacterial activity, but the non-polar extracts has not been studied yet. Therefore, this study aimed to determine the secondary metabolites of B. asiatica using a non-polar solvent (n-hexane) and evaluate its activity against Gram-positive and Gram-negative bacteria. The extraction method employed using soxhlet extraction, and the antibacterial activity was determined using the Kirby-Bauer method. The presence of secondary metabolites in the B. asiatica seed extract was assessed using phytochemical tests, and its chemical composition was analyzed using Gas Chromatography Mass Spectrophotometry (GC-MS). The yield of n-hexane extract from B. asiatica seeds was 1.7%, and the phytochemical analysis revealed that the B. asiatica seeds n-hexane extract contains only terpenoids compounds. The B. asistica seeds n-hexane extract at concentration of 10% (w/v) showed the highest zone of inhibition against Staphylococcus aureus (9.3 mm) followed by Escherichia coli (9,9 mm). The GC-MS analysis showed that B. asiatica seeds n-hexane extract contains Guaiene, Guaiene, Ledene, 9,12-Octadecadienoic acid, and Ethyl linoleate. Based on these findings, it can be concluded that B. asiatica seed's n-hexane extract exhibited antibacterial activity against S. aureus and E. coli.